DEFINING THE SEQUENCE OF INTEGRATING TRUSTWORTHINESS COMPONENTS INTO INFORMATION SECURITY SYSTEMS - Bakalynskyi, Oleksandr; Korobeynikov, Fedir (Ukrainian Information Security Research Journal, 2023)
The article explores the concept of trustworthiness as an approach to building information security systems, which helps to maintain trust in the information systems they protect. Key components of trustworthiness are identified and ranked: resilience, security, safety, privacy, and compliance. Attention is focused on the significance of the emergent interaction of these components, providing a justified percentage weight for each of them. Two approaches to creating trustworthy systems are considered: the integration of trustworthiness components into the system architecture at the design stage, and the adaptation of existing systems. The advantages and disadvantages of each approach are discussed in the context of implementation speed, cost-effectiveness, and alignment with the philosophy of trustworthiness.